Biometric Data Processing Based on Artificial Intelligence and the Principle of Accountability: A Comparative Study of Indonesia and European Union - Sinta Dewi; Audena Priscilla Sihombing; Tri Andika (Universitas Islam Sultan Agung, 2026)
Digital advances in Artificial Intelligence (AI) have accelerated the use of biometric data to speed up identification with high accuracy. However, the processing of biometric data raises serious privacy challenges, particularly regarding security and data controllers' accountability. Using normative juridical research methods with descriptive-analytical approaches, laws and regulations, legal doctrines, scientific literature, and practical cases, including World App, Holy Moment, and Clearview AI, this study aims to analyze the application of accountability principles in AI-based biometric data processing through a comparative study between Indonesia and the European Union. The findings indicate that in Indonesia, Law Number 27/2022 on Personal Data Protection (PDP Law) provide a legal basis for biometric data protection; however, its implementation remains constrained by weak supervision, the absence of derivative regulations, and limited understanding of privacy among the public and business actors. In contrast, the European Union, through the General Data Protection Regulation (GDPR) and the EU-AI Act, enforces a robust accountability principle supported by strict oversight and substantial sanctions, resulting in more effective protection of biometric data. The recommendations of this study include strengthening AI regulations and supervisory mechanisms in Indonesia to ensure that AI-based biometric data processing is conducted lawfully, transparently, and responsibly, while simultaneously fostering public trust in digital technologies.